2021
DOI: 10.3390/cells10061329
|View full text |Cite
|
Sign up to set email alerts
|

Targeting Natural Killer T Cells in Solid Malignancies

Abstract: Natural killer T (NKT) cells are a unique subset of lymphocytes that recognize lipid antigens in the context of the non-classical class I MHC molecule, CD1d, and serve as a link between the innate and adaptive immune system through their expeditious release of cytokines. Whereas NKT have well-established roles in mitigating a number of human diseases, herein, we focus on their role in cancer. NKT cells have been shown to directly and indirectly mediate anti-tumor immunity and manipulating their effector functi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
11
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 16 publications
(11 citation statements)
references
References 96 publications
0
11
0
Order By: Relevance
“…Moreover, NKT-like cells expressing prominent functional receptors NKp30, NKp46, and CD161 were reduced, whereas KIR2DL2/L3/S3+NKT-like cells were increased in the PF. It is also reported that NKT-like cells participate directly or indirectly in anti-tumor immunity [27]. Similar to NK cells, NKT-like cell activation depends on the balance between the stimulatory and inhibitory signals generated by the engagement of NCRs and KIRs to their cognate ligands [27].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Moreover, NKT-like cells expressing prominent functional receptors NKp30, NKp46, and CD161 were reduced, whereas KIR2DL2/L3/S3+NKT-like cells were increased in the PF. It is also reported that NKT-like cells participate directly or indirectly in anti-tumor immunity [27]. Similar to NK cells, NKT-like cell activation depends on the balance between the stimulatory and inhibitory signals generated by the engagement of NCRs and KIRs to their cognate ligands [27].…”
Section: Discussionmentioning
confidence: 99%
“…It is also reported that NKT-like cells participate directly or indirectly in anti-tumor immunity [27]. Similar to NK cells, NKT-like cell activation depends on the balance between the stimulatory and inhibitory signals generated by the engagement of NCRs and KIRs to their cognate ligands [27]. Thus, dysregulated receptor expression on tumor-associated NKT-like cells may impair their anti-tumor response.…”
Section: Discussionmentioning
confidence: 99%
“…Indeed, there is an increasing investigation in establishing an effective immune cell-based therapy for GC by ex vivo activating and expanding immune cells. Multifarious studies have presented the therapeutic potential of effective immunotherapy of immune cells ( Rezvani, Daher et al, 2020 ; Ingram, Madan et al, 2021 ).…”
Section: Introductionmentioning
confidence: 99%
“…To more selectively stimulate iNKT cells, one could use the therapeutic glycosphingolipid, a-galactosylceramide (a-GalCer), which is an immunomodulatory drug that very potently and specifically stimulates iNKT cells (27). Although initial studies showed great promise in activating iNKT cells to induce antitumoral effects (27)(28)(29), numerous clinical trials with various patients with solid tumor have only shown partial and inconsistent responses (30)(31)(32)(33)(34). Explanations for these disparate results included the development of iNKT-cell anergy with multiple a-GalCer stimulations, the potential patient pool which included patients with established solid tumors, and induction of resistance within the tumor to activated iNKT cells.…”
Section: Introductionmentioning
confidence: 99%